El Dispositivo del Dron: Entre la Vigilancia Securitaria y la Necropolítica - Mendiola Gonzalo, Ignacio (Convergencia, 2018)
Moving away from the growing techno-scientific fascination embodied by the drone, the main aim is to analyze the role played by this device in the context of the current security surveillance. Following to a great extent the conceptual approaches coming from critical security studies, we will address issues that refer to the redefinition of the surveillance provided by the scopic power of the drone, the military-police logics in which it is immersed in order to detect what has been defined as a threat and, finally, to the specific geographical reconfiguration of the sovereign power the drone activates within the framework of security surveillance. It will be concluded that, opposing the surgical warfare discourse that legitimizes the drone via its techno-scientific accuracy potential, this device reproduces a necro-political logic that must be exhibited and questioned from the violence it causes.El objetivo central del presente artículo es analizar el papel que juega el dron en el contexto de la actual vigilancia securitaria. Con base en gran parte de los planteamientos conceptuales de los estudios críticos de la seguridad, se abordarán cuestiones que remiten a la redefinición de la vigilancia que depara el poder escópico del dron, a las lógicas bélico-policiales en las cuales está inmerso, para detectar lo que queda definido como amenaza y, por último, a la específica reconfiguración geográfica del poder soberano que el dron activa en el marco de la vigilancia securitaria. Se concluirá que, frente al discurso de guerra quirúrgica que legitima al dron a través de su potencial tecnocientífico de precisión, este dispositivo reproduce una lógica necropolítica que ha de ser expuesta y cuestionada desde la violencia que ocasiona